Container containing polymerizable liquid crystal composition liquid and storage method of polymerizable liquid crystal composition liquid
By controlling the oxygen concentration in the container and adding an appropriate amount of polymerization inhibitor, the problems of orientation defects and chromatic deterioration of the polymerization liquid composition liquid in storage are solved, and a homogeneous and high polymerization rate liquid crystal cured layer is achieved, which is suitable for high optics Manufacturing of characteristic optical films.
Patent Information
- Application Number
- CN202010727376.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-30
- Filing Date
- 2020-07-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-07-24
AI Technical Summary
During the temporary or long-term storage process of the polymerizable liquid crystal composition liquid, the orientation defects, chromatic deterioration and a decrease in the polymerization rate of the liquid crystal cured layer are easily caused, and it is difficult to ensure the homogeneity of the produced liquid crystal cured layer.
A container containing a gas phase part and a liquid phase part is used, and the oxygen concentration in the gas phase part is controlled to be more than 0.05% by volume and less than 20.8% by volume, and includes a polymerizable liquid crystal compound, a free ketone solvent, an amide solvent, an ester solvent and an ether solvent. , photopolymerization initiator and polymerization inhibitor, the photopolymerization initiator content is 0.1 mass % or more and 2 mass % or less, the polymerization inhibitor content is 0.1 mass % or more and 2 mass % or less, and 10°C or more and 50°C or less custody under conditions of
It effectively prevents the coloring and polymerization reaction of the polymerizable liquid crystal composition liquid in storage, ensures the homogeneity and high polymerization rate of the liquid crystal cured layer, and is suitable for optical film fields that require high optical characteristics.
Smart Images

Figure BDA0002599893590000061 
Figure BDA0002599893590000091 
Figure BDA0002599893590000251
Abstract
Description
Technical Field
[0001] The present invention relates to a container containing a polymerizable liquid crystal composition liquid and a storage method of the polymerizable liquid crystal composition liquid. Background Art
[0002] In recent years, as image display devices have become thinner, optical films such as phase difference films including a liquid crystal solidified layer obtained by coating a polymerizable liquid crystal compound on a substrate or an alignment film and solidifying it in an oriented state are being developed. In the manufacture of such optical films, from the viewpoints of film forming properties and handling properties, the polymerizable liquid crystal compound is usually coated on the substrate or the alignment film in the form of a polymerizable liquid crystal composition liquid obtained by dissolving the polymerizable liquid crystal compound in a solvent or the like.
[0003] In actual production sites of optical films, polymerizable liquid crystal composition liquid is sometimes temporarily or long-term filled in a container and stored before being used to produce a liquid crystal cured layer, and various organic material containers for storing or transporting such liquid organic materials have been proposed (e.g., Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2016 / 052060 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] If a liquid crystal solidification layer is manufactured using a polymerizable liquid crystal composition liquid obtained by temporarily or long-term storage of a polymerizable liquid crystal compound dissolved in a solvent, defects may occur in the orientation of the liquid crystal solidification layer, or oxides may be generated to deteriorate the hue, or the polymerization rate may be reduced, and it may sometimes become difficult to ensure the homogeneity of the manufactured liquid crystal solidification layer.
[0009] Therefore, an object of the present invention is to provide a container containing a polymerizable liquid crystal composition liquid suitable for storing a polymerizable liquid crystal composition liquid for obtaining a liquid crystal solidified layer that is homogeneous and less likely to have alignment defects during temporary or long-term storage.
[0010] Solutions for solving problems
[0011] The present invention includes the following preferred embodiments.
[0012] [1] a container containing a polymerizable liquid crystal composition liquid, the container comprising a gas phase and a liquid phase formed of the polymerizable liquid crystal composition liquid,
[0013] The polymerizable liquid crystal composition liquid comprises: a polymerizable liquid crystal compound; one or more solvents selected from the group consisting of a ketone solvent, an amide solvent, an ester solvent, and an ether solvent; a photopolymerization initiator; and a polymerization inhibitor in an amount of 0.1% by mass or more and 2% by mass or less relative to the polymerizable liquid crystal compound.
[0014] The oxygen concentration in the gas phase is not less than 0.05 volume % and not more than 20.8 volume %.
[0015] [2] The container containing the polymerizable liquid crystal composition liquid according to [1] above, wherein the polymerizable liquid crystal compound has a (meth)acryloyl group.
[0016] [3] The container containing the polymerizable liquid crystal composition liquid according to [1] or [2] above, wherein the polymerizable liquid crystal compound exhibits maximum absorption in a wavelength range of 300 nm to 400 nm.
[0017] [4] The container containing the polymerizable liquid crystal composition liquid according to any one of [1] to [3] above, wherein the polymerization inhibitor comprises at least one selected from the group consisting of phenolic compounds and amine compounds.
[0018] [5] The container containing the polymerizable liquid crystal composition liquid according to any one of [1] to [4] above, wherein the oxygen concentration in the gas phase is 0.1% by volume or more and 10% by volume or less.
[0019] [6] The container containing the polymerizable liquid crystal composition liquid according to any one of [1] to [5] above, wherein the total light transmittance of the container is 20% or less.
[0020] [7] A method for storing a polymerizable liquid crystal composition liquid, comprising storing the polymerizable liquid crystal composition liquid in a container in an atmosphere having an oxygen concentration of not less than 0.05 volume % and not more than 20.8 volume %, wherein the polymerizable liquid crystal composition liquid comprises: a polymerizable liquid crystal compound; one or more solvents selected from the group consisting of a ketone solvent, an amide solvent, an ester solvent, and an ether solvent; a photopolymerization initiator; and an inhibitor in an amount of not less than 0.1 mass % and not more than 2 mass % relative to the polymerizable liquid crystal compound.
[0021] [8] The method for storing a polymerizable liquid crystal composition liquid according to [7] above, wherein the liquid crystal composition liquid is stored in a container having a total light transmittance of 20% or less.
[0022] [9] The method for storing a polymerizable liquid crystal composition liquid according to [7] or [8] above, wherein the storage is performed at a temperature of 10° C. to 50° C.
[0023] Effects of the Invention
[0024] According to the present invention, a container containing a polymerizable liquid crystal composition liquid suitable for storing a polymerizable liquid crystal composition liquid for obtaining a liquid crystal solidified layer which is homogeneous and hardly causes alignment defects during temporary or long-term storage can be provided. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.
[0026] <Container containing polymerizable liquid crystal composition liquid>
[0027] The container containing the polymerizable liquid crystal composition liquid of the present invention comprises a gas phase and a liquid phase formed by the polymerizable liquid crystal composition liquid. That is, the "container containing the polymerizable liquid crystal composition liquid" in the present invention refers to a container in which there are a gas phase and a liquid phase formed by the polymerizable liquid crystal composition liquid.
[0028] (A) Gas phase
[0029] The gas phase is composed of a gas containing oxygen. In the present invention, the oxygen concentration of the gas phase is 0.05 volume % or more and 20.8 volume % or less relative to the volume occupied by the gas phase in the container containing the polymerizable liquid crystal composition liquid. By making the oxygen concentration of the gas phase below 20.8 volume %, it is possible to suppress the coloring (yellowing) of the polymerizable liquid crystal composition liquid that may occur due to the generation of peroxides over time in the polymerizable liquid crystal composition liquid. Thus, it is possible to prevent the coloring of the liquid crystal solidified layer formed by the polymerizable liquid crystal composition liquid. In addition, by making the oxygen concentration of the gas phase above 0.05 volume %, the polymerization inhibitor contained in the polymerizable liquid crystal composition liquid fully functions, and the polymerization of the polymerizable liquid crystal compound in the composition liquid can be effectively suppressed. Thus, it is possible to suppress the orientation defects caused by the polymer formed in the composition liquid to form a homogeneous liquid crystal solidified layer. The oxygen concentration in the gas phase is preferably 20 volume % or less, more preferably 10 volume % or less, further preferably 5 volume % or less, particularly preferably 3 volume % or less, and preferably 0.08 volume % or more, more preferably 0.1 volume % or more.
[0030] The oxygen concentration in the gas phase can be measured, for example, using an oxygen concentration meter. The oxygen concentration in a container filled with a liquid phase can be measured and controlled by the following methods: replacing the gas in the container with an inert gas until the oxygen concentration in the gas phase reaches a specified concentration; degassing in a vacuum atmosphere to bring the oxygen concentration to a specified concentration; replacing the oxygen concentration with a gas mixed with oxygen and an inert gas to bring the oxygen concentration into a specified range; and the like.
[0031] Examples of the inert gas include rare gases such as nitrogen, helium, and argon, and mixtures thereof. From the viewpoint of economic efficiency and ease of handling, nitrogen is preferably used.
[0032] (B) Liquid phase
[0033] The liquid phase is formed by a polymerizable liquid crystal composition liquid. In the present invention, the polymerizable liquid crystal composition liquid contains a polymerizable liquid crystal compound, a solvent, a photopolymerization initiator, and a polymerization inhibitor. The components contained in the polymerizable liquid crystal composition liquid of the present invention are described in detail below.
[0034] (Polymerizable Liquid Crystal Compound)
[0035] The polymerizable liquid crystal composition liquid contains a polymerizable liquid crystal compound. In the present invention, the polymerizable liquid crystal compound refers to a liquid crystal compound containing a polymerizable functional group, and a liquid crystal compound having a photopolymerizable functional group is particularly preferred. The photopolymerizable functional group refers to a group that can participate in a polymerization reaction due to active free radicals, acids, etc. generated by the photopolymerization initiator described later. As the photopolymerizable functional group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth)acryloyl (i.e., methacryloyl or acryloyl), oxirane, oxetane, etc. can be cited. Among them, (meth)acryloyl is preferred. The liquid crystal can be a thermotropic liquid crystal or a lyotropic liquid crystal. As a phase-ordered structure, it can be a nematic liquid crystal or a smectic liquid crystal. As a polymerizable liquid crystal compound, only one type can be used, or two or more types can be used in combination.
[0036] For the container containing the polymerizable liquid crystal composition liquid of the present invention in which the polymerizable liquid crystal compound exists at a specific oxygen concentration, the coloring of the polymerizable liquid crystal composition liquid during storage and the generation of orientation defects caused by the polymerization of the polymerizable liquid crystal compound can be suppressed. Therefore, the present invention can be widely used in the field of optical films requiring high optical properties and excellent appearance using polymerizable liquid crystal composition liquids of previously known polymerizable liquid crystal compounds. From the viewpoint of optical properties, as polymerizable liquid crystal compounds, for example, compounds satisfying the following (1) to (4) can be cited.
[0037] (1) A compound that can form a nematic phase or a smectic phase.
[0038] (2) The polymerizable liquid crystal compound has π electrons in the long axis direction (a).
[0039] (3) It has π electrons in a direction intersecting the long axis direction (a) (intersecting direction (b)).
[0040] (4) The total number of π electrons present in the long axis direction (a) is N(πa), the total number of molecular weights present in the long axis direction is N(Aa), and the π electron density in the long axis direction (a) of the polymerizable liquid crystal compound is defined by the following formula (i):
[0041] D(πa)=N(πa) / N(Aa) (i)
[0042] The π electron density in the cross direction (b) of the polymerizable liquid crystal compound is defined by the following formula (ii), where the total number of π electrons present in the cross direction (b) is N(πb) and the total molecular weight present in the cross direction (b) is N(Ab):
[0043] D(πb)=N(πb) / N(Ab) (ii)
[0044] Existential form (iii)
[0045] 0≤〔D(πa) / D(πb)〕<1 (iii)
[0046] The relationship between the π electron density in the cross direction (b) and the π electron density in the long axis direction (a) is greater. In addition, as described above, polymerizable liquid crystal compounds having π electrons in the long axis and in the cross direction relative to the long axis are usually easy to form a T-shaped structure.
[0047] In the above-mentioned features (1) to (4), the major axis direction (a) and the number of π electrons N are defined as follows.
[0048] The major axis direction (a) refers to the major axis direction of the rod, for example, in the case of a compound having a rod-like structure.
[0049] The number of π electrons N(πa) present in the major axis direction (a) does not include π electrons that disappear due to the polymerization reaction.
[0050] The number of π electrons N(πa) existing in the long axis direction (a) is the total number of π electrons on the long axis and π electrons conjugated thereto, for example, including the number of π electrons existing in the ring existing in the long axis direction (a) and satisfying the Huckel rule.
[0051] The number of π electrons N(πb) existing in the crossing direction (b) does not include π electrons that disappear due to the polymerization reaction.
[0052] The polymerizable liquid crystal compound satisfying the above conditions has a mesostructure in the long-axis direction, and exhibits a liquid crystal phase (nematic phase, smectic phase) due to the mesostructure.
[0053] The polymerizable liquid crystal compound satisfying the above (1) to (4) can form a nematic phase or a smectic phase by being coated on a substrate or an alignment film and heated to a temperature above the phase transition temperature. The nematic phase or the smectic phase formed by the orientation of the polymerizable liquid crystal compound is usually oriented in a manner that the long axis directions of the polymerizable liquid crystal compound are parallel to each other, and the long axis direction becomes the orientation direction of the nematic phase. If such a polymerizable liquid crystal compound is made into a film and polymerized in a nematic phase or a smectic phase, a polymer film formed by polymerizing in a state oriented along the long axis direction (a) can be formed. The polymer film absorbs ultraviolet rays by π electrons in the long axis direction (a) and π electrons in the cross direction (b). Here, the maximum absorption wavelength of ultraviolet rays absorbed by the π electrons in the cross direction (b) is recorded as λbmax. λbmax is usually 300nm to 400nm. The density of π electrons satisfies the above formula (iii), and the density of π electrons in the cross direction (b) is greater than that in the long axis direction (a), so that the absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the cross direction (b) is greater than that of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the long axis direction (a). The ratio (absorbance in the cross direction (b) of linearly polarized ultraviolet light / absorbance in the long axis direction (a)) is, for example, greater than 1.0, preferably greater than 1.2, and usually 30 or less, for example, 10 or less.
[0054] For the polymerizable liquid crystal compound having the above characteristics, usually, the birefringence of the polymer in its oriented state mostly exhibits reverse wavelength dispersion. From the viewpoint of easily obtaining a liquid crystal solidified layer with better optical properties, the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition liquid in the present invention preferably exhibits reverse wavelength dispersion.
[0055] Specific examples of such polymerizable liquid crystal compounds include compounds represented by the following formula (A1):
[0056]
[0057] In formula (A1), Ar represents a divalent group containing an aromatic group which may have a substituent. The aromatic group mentioned here refers to a group having a π electron number of [4n+2] in the ring structure according to the Huckel rule, for example, an Ar group as exemplified by (Ar-1) to (Ar-23) described later may have two or more Ar groups with the aid of a divalent linking group. Here, n represents an integer. In the case where a ring structure is formed by containing heteroatoms such as -N= and -S-, the case where the non-covalent electron pairs on these heteroatoms satisfy the Huckel rule and thus have aromaticity is also included. It is preferred that at least one of a nitrogen atom, an oxygen atom, and a sulfur atom is contained in the aromatic group. The aromatic group contained in the divalent group Ar may be one or more. In the case where the aromatic group is one, the divalent group Ar may be a divalent aromatic group which may have a substituent. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a single bond, a divalent bonding group such as -CO-O-, or -O-.
[0058] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.
[0059] L 1 and L 2 Each is independently a divalent linking group having an ester structure.
[0060] B 1 and B 2 Each is independently a single bond or a divalent linking group.
[0061] k and l each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.
[0062] E 1 and E 2Each independently represents an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. In addition, the hydrogen atoms contained in the alkanediyl group may be substituted with halogen atoms, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S-, -SiH2-, or -C(=O)-.
[0063] P 1 and P 2 Each independently represents a photopolymerizable group or a hydrogen atom, and at least one of them is a (meth)acryloyl group.
[0064] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms. More preferably, it is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group. Especially preferably, it is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.
[0065] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.
[0066] L 1 and L 2 Each is independently preferably -R a1 COOR a2 -(R a1 and R a2 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms), more preferably -COOR a2-1 -(R a2-1 It represents a single bond, -CH2-, or -CH2CH2-), and is more preferably -COO- or -COOCH2CH2-.
[0067] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a3 OR a4 -、-R a5 COOR a6-、-R a7 OCOR a8 -, or -R a9 OC=OOR a10 -. Here, R a3 ~R a10 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a4-1 -、-CH2-、-CH2CH2-、-COOR a6-1 -, or -OCOR a8-1 -. Here, R a4-1 , R a6-1 , R a8-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO- or -OCOCH2CH2-.
[0068] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, k+l=4 is preferred, and k=2 and l=2 are more preferred. k=2 and l=2 are preferred because a symmetrical structure is obtained.
[0069] As P 1 or P 2 Examples of the photopolymerizable group include epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyl, methacryloyl, oxiranyl, and oxetanyl. 1 or P 2 At least one of them is acryloyl or methacryloyl, preferably P 1 and P 2 All are acryloyl or methacryloyl, and acryloyl is more preferred.
[0070] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring, etc. can be cited. Among them, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazolyl. In addition, when Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.
[0071] In formula (A1), the total number of π electrons contained in the divalent aromatic group represented by Ar is N π It is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0072] Examples of the aromatic group represented by Ar include the following groups.
[0073]
[0074] In the formulas (Ar-1) to (Ar-23), the symbol * represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0075] Q 1 and Q 2 Each independently represents -CR 1’ R 2’ -、-S-、-NH-、-NR 1’ -, -CO- or -O-, R 1’ and R 2’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0076] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0077] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0078] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0079] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes an aromatic hydrocarbon group having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes an aromatic heterocyclic group having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contains at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.
[0080] Y 1 , Y 2 and Y 3 Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.
[0081] Z 0 , Z 1 and Z 2 Each of them is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkoxy group having 1 to 12 carbon atoms, 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferably, Z is a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 A polymerizable group may be contained.
[0082] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 1’ -、-O-,R 1’A hydrogen atom is preferred, and among them, -S-, -O-, and -NH- are particularly preferred.
[0083] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0084] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic rings that Ar may have and are described above, for example, a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, a pyrrolidine ring, etc. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.
[0085] The polymerizable liquid crystal compound preferably exhibits a maximum absorption (λ) in a wavelength range of 300 nm to 400 nm, more preferably in a wavelength range of 315 nm to 385 nm, and further preferably in a wavelength range of 320 nm to 380 nm. max ). In the present invention, the polymerizable liquid crystal composition liquid contains a photopolymerization initiator, so it becomes easy to undergo polymerization reaction and gelation during storage. By making the polymerizable liquid crystal compound show maximum absorption in the range of wavelengths above 300nm and below 400nm, it is possible to prevent polymerization reaction and gelation during storage and make long-term storage possible. It should be noted that when the maximum absorption wavelength of the polymerizable liquid crystal compound is above 300nm, there is a tendency for the liquid crystal solidified layer composed of the polymer in the oriented state of the polymerizable liquid crystal compound to easily show reverse wavelength dispersion. When the maximum absorption wavelength of the polymerizable liquid crystal compound is below 400nm, the absorption in the visible light region is suppressed, so the coloring of the liquid crystal solidified layer can be suppressed. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured by using a UV visible spectrophotometer in a solvent that can dissolve the polymerizable liquid crystal compound.
[0086] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition liquid can be appropriately selected according to the type and content of the polymerizable liquid crystal compound, as well as the solvent, photopolymerization initiator and polymerization inhibitor. In one embodiment of the present invention, the content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition liquid is preferably 70 parts by mass or more and 99.5 parts by mass or less relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition liquid, more preferably 80 parts by mass or more and 99 parts by mass or less, and further preferably 90 parts by mass or more and 98 parts by mass or less. Here, the solid content in the present invention refers to the total of the components after removing volatile components such as solvents from the polymerizable liquid crystal composition liquid.
[0087] (Solvent)
[0088] The polymerizable liquid crystal composition liquid includes one or more solvents selected from the group consisting of ketone solvents, amide solvents, ester solvents and ether solvents. The solvent selected from the aforementioned group generates active free radicals in the presence of oxygen, thereby making the inhibitor simultaneously contained in the polymerizable liquid crystal composition liquid function, which can help to suppress the polymer formation of the polymerizable liquid crystal compound. On the other hand, these solvents will produce peroxides in the presence of oxygen, so the solvent itself has a tendency to easily color (yellowing) over time. In the present invention, by controlling the oxygen concentration of the gas phase to a specific range, the coloring of the polymerizable liquid crystal composition liquid is suppressed and the oxygen concentration required for the inhibitor to function is ensured, so that even when the polymerizable liquid crystal composition liquid is temporarily or long-term stored, the polymer formation of the polymerizable liquid crystal compound and the coloring of the polymerizable liquid crystal composition liquid can be effectively suppressed. For these solvents, it is possible to appropriately select a solvent that can dissolve the polymerizable liquid crystal compound used and is inactive relative to the polymerizable liquid crystal compound according to the type of the polymerizable liquid crystal compound used. These solvents can be used alone or in combination.
[0089] In the present invention, the ketone solvent refers to a solvent containing -CO- and no -COO- in the molecule, and examples thereof include acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, cycloheptanone, methyl amyl ketone, methyl isobutyl ketone, N-methyl-2-pyrrolidone, and the like.
[0090] Examples of the amide solvent include organic solvents having an amide bond in the molecule, such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.
[0091] In the present invention, the ester solvent refers to a solvent containing -COO- in the molecule, for example, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, butyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate and diethylene glycol monobutyl ether acetate.
[0092] In the present invention, the ether solvent refers to a solvent containing -O- and not containing -COO- in the molecule, and examples thereof include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, 3-methoxy-1-butanol, 3-methoxy-3-methylbutanol, tetrahydrofuran, tetrahydropyran, 1,4-dioxane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, and dimethoxyethane.
[0093] In one embodiment of the present invention, the content of the solvent in the polymerizable liquid crystal composition liquid is preferably greater than 10 parts by mass and less than 10,000 parts by mass, more preferably greater than 50 parts by mass and less than 5,000 parts by mass, and further preferably greater than 500 parts by mass and less than 3,000 parts by mass, relative to 100 parts by mass of the solid component of the polymerizable liquid crystal composition liquid.
[0094] (Photopolymerization Initiator)
[0095] The polymerizable liquid crystal composition liquid contains a photopolymerization initiator. When the polymerizable liquid crystal composition liquid of the present invention is irradiated with light, the polymerizable liquid crystal compound in the liquid starts to polymerize.
[0096] The type of photopolymerization initiator can be appropriately selected according to the polymerizable liquid crystal compound used, and is not particularly limited. As the photopolymerization initiator, for example, oxime compounds, benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts and sulfonium salts can be cited. The photopolymerization initiator can be used alone or in combination of two or more.
[0097] Examples of the benzoin compound include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether. Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4′-methyldiphenyl sulfide, 3,3′,4,4′-tetrakis(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone. Examples of the alkylphenone compound include diethoxyacetophenone, 2-methyl-2-morpholinyl-1-(4-methylthiophenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)butane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propane-1-one, 1-hydroxycyclohexylphenylketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane-1-one. Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and the like. Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(2-(5-methylfuran-2-yl)-1,3,5-triazine, [vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)vinyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)vinyl]-1,3,5-triazine, etc.
[0098] As the oxime compound, for example, a triazine compound or a carbazole compound having an oxime structure is preferred, and from the viewpoint of sensitivity, a carbazole compound having an oxime ester structure is more preferred. Examples of the carbazole compound having an oxime structure include 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime).
[0099] As the photopolymerization initiator, a commercially available photopolymerization initiator can be used. Examples of commercially available photopolymerization initiators include "Irgacure (registered trademark) 907", "Irgacure (registered trademark) 184", "Irgacure (registered trademark) 651", "Irgacure (registered trademark) 819", "Irgacure (registered trademark) 250", "Irgacure (registered trademark) 369", "Irgacure (registered trademark) OXE-01", "Irgacure (registered trademark) OXE-02", and "Irgacure (registered trademark) OXE-03" (manufactured by BASF Japan Ltd.); "SEIKUOL (registered trademark) BZ", "SEIKUOL (registered trademark) Z", and "SEIKUOL (registered trademark) BEE" (Seiko Chemical Industries, Ltd.); "kayacure (registered trademark) BP100" (Nippon Kayaku Co., Ltd.); "kayacure (registered trademark) UVI-6992" (manufactured by Dow Inc.); "Adekaoptomer SP-152", "AdekaoptomerSP-170", "Adekaoptomer N-1919", "ADEKA ARKLS NCI-831" (ADEKA Co., Ltd.); "TAZ-A", "TAZ-PP" (Japanese Siber Hegner Company); and "TAZ-104" (SANWA CHEMICAL CO., LTD.), etc.
[0100] The content of the photopolymerization initiator in the polymerizable liquid crystal composition liquid can be appropriately adjusted according to the type and content of the polymerizable liquid crystal compound and the polymerization inhibitor contained in the composition liquid. For example, the content of the photopolymerization initiator is preferably 0.1 mass parts or more and 30 mass parts or less relative to 100 mass parts of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition liquid, and more preferably 0.5 mass parts or more and 10 mass parts or less. If the content of the photopolymerization initiator is within such a range, when the polymerizable liquid crystal composition liquid is used, the reaction of the polymerizable group of the polymerizable liquid crystal compound will be fully carried out, and it is not easy to confuse the orientation of the polymerizable liquid crystal compound.
[0101] (Inhibitor)
[0102] The polymerizable liquid crystal composition liquid in the present invention contains a polymerization inhibitor. The container containing the polymerizable liquid crystal composition liquid of the present invention contains the polymerizable liquid crystal composition liquid containing a predetermined amount of polymerization inhibitor and the gas phase controlled to the above-mentioned specific oxygen concentration, so that the polymerizable liquid crystal composition liquid in the storage can be stored for a long time in a state where the polymerization reaction of the polymerizable liquid crystal compound is suppressed. Thus, the generation of alignment defects when the liquid crystal solidified layer is formed by the polymerizable liquid crystal compound can be suppressed while ensuring a high polymerization rate of the polymerizable liquid crystal compound.
[0103] The polymerization inhibitor can be appropriately selected according to the polymerizable liquid crystal compound, solvent and photopolymerization initiator constituting the polymerizable liquid crystal composition liquid. As the polymerization inhibitor, for example, phenolic compounds, amine compounds, sulfur compounds, phosphorus compounds, etc. can be cited. They can be used alone or in combination of two or more.
[0104] Among these, from the perspective of more effectively suppressing the polymerization reaction of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition liquid, less likely to produce orientation defects, and easily obtaining a uniform liquid crystal solidified layer, it is preferred that the inhibitor include one or more selected from the group consisting of phenolic compounds and amine compounds.
[0105] Examples of the phenolic compound include 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 2,2'-methylenebis(6-tert-butyl-4-methylphenol), 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 4,4'-thiobis(2-tert-butyl-5-methylphenol), 2,2'-thiobis(6-tert-butyl-4-methylphenol), phenol), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,6-di-tert-butyl-4-methylphenol and 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin, etc. Alternatively, a commercially available phenolic inhibitor (antioxidant) may be used.
[0106] Examples of the amine compound include N,N'-di-sec-butyl-p-phenylenediamine, N,N'-diisopropyl-p-phenylenediamine, N,N'-dicyclohexyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, and N,N'-bis(2-naphthyl)-p-phenylenediamine. Alternatively, a commercially available amine-based polymerization inhibitor (antioxidant) may be used.
[0107] In the present invention, the polymerizable liquid crystal composition liquid contains a polymerization inhibitor in an amount of 0.1% by mass or more and 2% by mass or less relative to the polymerizable liquid crystal compound. By containing a polymerization inhibitor in the presence of a gas phase controlled to be the above-mentioned specific oxygen concentration, in an amount of 0.1% by mass or more relative to the polymerizable liquid crystal compound, the polymerization reaction in the storage can be suppressed, and the oxidation of the polymerizable liquid crystal compound can be suppressed. By containing a polymerization inhibitor in an amount of 2% by mass or less relative to the polymerizable liquid crystal compound, the influence on the polymerization rate of the polymerizable liquid crystal compound after storage can be suppressed, and a high polymerization rate can be ensured. In the present invention, the amount of the polymerization inhibitor is preferably 0.15% by mass or more, more preferably 0.2% by mass or more, and more preferably 0.3% by mass or more. Furthermore, the amount of the polymerization inhibitor in the present invention is preferably 1.9% by mass or less, more preferably 1.5% by mass or less, more preferably 1.3% by mass or less, more preferably 1.2% by mass or less, and particularly preferably 1% by mass or less.
[0108] (Other ingredients)
[0109] The polymerizable liquid crystal composition liquid may contain other additives such as a photosensitizer and a leveling agent as appropriate. The additives may be used alone or in combination of two or more.
[0110] By using a photosensitizer, the photopolymerization initiator can be made highly sensitive. Examples of the photosensitizer include xanthone, thioxanthone and other xanthones, anthracene and anthracenes having a substituent such as an alkyl ether, phenothiazine, rubrene, and the like. The photosensitizer can be used alone or in combination of two or more.
[0111] The content of the photosensitizer is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and further preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0112] The leveling agent is an additive that has the function of adjusting the fluidity of the polymerizable liquid crystal composition liquid and making the liquid crystal cured layer obtained by applying the composition liquid flatter. For example, silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents such as silane coupling agents can be cited. Specifically, DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, and FZ2123 (all of the above are from Dow Corning Toray Co., Ltd.(made), KP321, KP323, KP324, KP326, KP340, KP341, 403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE-502, KBE-503, KBM-5103, KBM-602, KBM-603, KBM-903 、KBE-903、KBE-9103、KBM-573、KBM-575、KBE-585、KBM-802、KBM-802、KBM-803、KBE-846、KBE-9007(All of the above are made by Shin-Etsu Chemical Co., Ltd.), TSF400、TSF401、TSF410、TSF4300、TSF4440、TSF4445、TSF-4446、TSF4452、TSF4460(All of the above are made by Momentive Performance Materials Japan LLC), Fluorinert (registered trademark) FC-72, Fluorinert FC-40, Fluorinert FC-43, Fluorinert FC-3283 (all manufactured by Sumitomo 3M Limited), MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAFACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-477, MEGAFACE F-479, MEGAFACE F-482, MEGAFACE F-483 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF303, EFTOP EF351, EFTOP EF352 (all of the above are manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all of the above are manufactured by AGC Seimi Chemical Co., Ltd.The leveling agent may be used alone or in combination of two or more. The content of the leveling agent may be preferably 0.01 parts by mass or more and 5 parts by mass or less, and more preferably 0.05 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound. .
[0113] The polymerizable liquid crystal composition liquid can be manufactured, for example, by stirring and mixing a polymerizable liquid crystal compound, a solvent, a photopolymerization initiator, an inhibitor, and additives as needed. The aforementioned stirring and mixing is preferably carried out in an atmosphere of low oxygen concentration, for example, an atmosphere of oxygen concentration of 0.1 volume % or more and 4 volume % or less. In addition, when the polymerizable liquid crystal composition liquid is stirred and mixed, by operating in an atmosphere with a lower oxygen concentration, the dissolution of the polymerizable liquid crystal compound in the solvent can be promoted, and even if the surrounding gas is involved in the liquid, the dissolved oxygen concentration of the obtained polymerizable liquid crystal composition liquid can be suppressed.
[0114] As the machine for mixing the polymerizable liquid crystal compound, solvent etc., it is possible to suitably select a machine known in the past in the field and use it. In addition, stirring / mixing conditions (e.g., stirring speed, temperature, time, etc.) can be suitably selected according to the type of the polymerizable liquid crystal compound, solvent, stirring / mixing machine etc. used.
[0115] The material constituting the container containing the polymerizable liquid crystal composition liquid of the present invention is not particularly limited as long as the function of the polymerizable liquid crystal composition liquid filled in the container is not impaired.
[0116] For example, as the material of the container, metal materials, resin materials or glass materials can be cited. Among them, in order to easily suppress the polymerization reaction of the polymerizable liquid crystal compound caused by the irradiation of light during the storage of the polymerizable liquid crystal composition liquid, a material with low light transmittance is preferred. As such a material, a metal material is more preferably a metal material with light shielding properties, for example, corrosion-resistant steel, titanium metal, titanium alloy, etc., light-shielding glass, etc. can be cited.
[0117] The total light transmittance of the container is preferably 20% or less, more preferably 15% or less, further preferably 13% or less, further preferably 10% or less, and particularly preferably 5% or less. It is preferred that the total light transmittance of the container as a whole is within the aforementioned range. The total light transmittance of the container can be measured, for example, in accordance with JIS K7105:1981. By making the total light transmittance of the container lower, the progress of the polymerization reaction can be suppressed, so there is no need to store the container containing the polymerizable liquid crystal composition liquid in, for example, a dark place, and it can be directly stored and transported even in a bright place.
[0118] The container containing the polymerizable liquid crystal composition liquid of the present invention is preferably filled with the polymerizable liquid crystal composition liquid in a capacity of preferably 40% or more and 99% or less, more preferably 50% or more and 98% or less, further preferably 60% or more and 97% or less, further preferably 70% or more and 96% or less, and particularly preferably 75% or more and 95% or less. When the filling amount of the polymerizable liquid crystal composition liquid is within the above range, it can be appropriately stored and transported without deteriorating the function of the polymerizable liquid crystal composition liquid in the container.
[0119] After the polymerizable liquid crystal composition liquid is filled into the container, the oxygen concentration in the gas phase in the container is controlled and the container is appropriately sealed with a lid, etc., thereby the container containing the polymerizable liquid crystal composition liquid of the present invention can be manufactured. The oxygen concentration in the gas phase in the container can be adjusted at any stage before or after the container is sealed with a lid, etc.
[0120] <Storage Method of Polymerizable Liquid Crystal Composition Liquid>
[0121] The storage method of the polymerizable liquid crystal composition liquid of the present invention comprises storing the polymerizable liquid crystal composition liquid in a container in an atmosphere with an oxygen concentration of not less than 0.05 volume % and not more than 20.8 volume %, wherein the polymerizable liquid crystal composition liquid comprises: a polymerizable liquid crystal compound; one or more solvents selected from the group consisting of ketone solvents, amide solvents, ester solvents and ether solvents; a photopolymerization initiator; and an inhibitor in an amount of not less than 0.1 mass % and not more than 2 mass % relative to the polymerizable liquid crystal compound.
[0122] The types and contents of the polymerizable liquid crystal compound, solvent, photopolymerization initiator and inhibitor in the polymerizable liquid crystal composition liquid, the method for producing the polymerizable liquid crystal composition liquid, and the details of the container used for storage are the same as those described in the container containing the polymerizable liquid crystal composition liquid of the above-mentioned present invention.
[0123] In the storage method of the polymerizable liquid crystal composition liquid of the present invention, the polymerizable liquid crystal composition liquid containing a specific amount of an inhibitor is stored in an oxygen concentration atmosphere within a specific range in the same manner as the container containing the polymerizable liquid crystal composition liquid of the present invention described above, thereby preventing the coloring of the polymerizable liquid crystal composition liquid during temporary or long-term (for example, for more than 6 months) storage and allowing the inhibitor to fully function, thereby inhibiting the progress of the polymerization reaction of the polymerizable liquid crystal compound and inhibiting the reduction in the polymerization rate of the polymerizable liquid crystal compound after storage.
[0124] In the storage method of the polymerizable liquid crystal composition liquid of the present invention, the polymerizable liquid crystal composition liquid is preferably stored below 50°C. By storing the polymerizable liquid crystal composition liquid below 50°C, the polymerization reaction of the polymerizable liquid crystal compound in storage can be more effectively suppressed. The polymerizable liquid crystal composition liquid is more preferably stored below 40°C, further preferably below 35°C, and further preferably below 30°C. In addition, the polymerizable liquid crystal composition liquid is preferably stored above 10°C. By storing the polymerizable liquid crystal composition liquid above 10°C, it is possible to suppress the situation in which the function of the polymerizable liquid crystal compound is damaged due to freezing of the polymerizable liquid crystal composition liquid. The storage temperature of the polymerizable liquid crystal composition liquid is more preferably above 15°C and below 40°C, and further preferably above 20°C and below 30°C.
[0125] For the polymerizable liquid crystal composition liquid in the container containing the polymerizable liquid crystal composition liquid of the present invention, the polymerizable liquid crystal composition liquid stored in the container for a certain period of time, and the polymerizable liquid crystal composition liquid stored by the storage method of the polymerizable liquid crystal composition liquid of the present invention, it is not easy to produce polymers of the polymerizable liquid crystal compound during storage due to the storage stability based on the effect of the present invention, and the generation of orientation defects caused by this can be suppressed, and the coloring of the polymerizable liquid crystal composition liquid can also be prevented. Therefore, it is suitable for the manufacture of liquid crystal solidification layers in the field of optical films that require high optical properties and excellent appearance.
[0126] The liquid crystal solidified layer can be produced from the polymerizable liquid crystal composition liquid in the container containing the polymerizable liquid crystal composition liquid of the present invention, the polymerizable liquid crystal composition liquid stored in the container for a certain period of time, etc. by the following method, the method comprising, for example, the following steps:
[0127] A step of coating a polymerizable liquid crystal composition liquid on a substrate or an alignment film to obtain a coating layer (hereinafter also referred to as a "coating step");
[0128] a step of removing the solvent from the coating layer obtained in the coating step to align the polymerizable liquid crystal compound (hereinafter also referred to as a "drying step"); and
[0129] A step of polymerizing the polymerizable liquid crystal compound aligned in the drying step to cure the polymerizable liquid crystal layer to obtain a liquid crystal cured layer (hereinafter also referred to as a “curing step”).
[0130] As the method of coating the polymerizable liquid crystal composition liquid on the substrate, there can be enumerated an extrusion coating method, a direct gravure coating method, a reverse gravure coating method, a CAP coating method, a slit coating method, a die coating method, etc. In addition, there can also be enumerated a method of coating using a coating machine such as a dip coater, a rod coater, a spin coater, etc.
[0131] Among them, from the aspect of being able to be continuously coated in a roll-to-roll form, CAP coating method, inkjet method, dip coating method, slit coating method, die coating method and coating method using a rod coater are preferred. In the case of coating in a roll-to-roll form, a photo-alignment film-forming composition or the like may be coated on a substrate to form an alignment film, and then a polymerizable liquid crystal composition liquid may be continuously coated on the obtained alignment film.
[0132] The substrate is preferably a resin substrate. As the resin constituting the substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose ester; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; and polyphenylene oxide (polyphenylene oxide) can be cited. Among them, a substrate formed of polyolefins such as polyethylene, polypropylene, and norbornene polymers is preferred.
[0133] An alignment film may be formed on the surface of the substrate on which the polymerizable liquid crystal composition liquid is applied. The alignment film has an alignment control force to align the polymerizable liquid crystal compound in a desired direction.
[0134] As an alignment film, it is preferred that the alignment film has solvent resistance such that the alignment film is not dissolved by the application of the polymerizable liquid crystal composition liquid, and has heat resistance to the removal of the solvent described later and the heating treatment for the alignment of the polymerizable liquid crystal compound. As alignment films, alignment films including alignment polymers, photoalignment films, and groove alignment films having a concave-convex pattern and a plurality of grooves on the surface can be cited.
[0135] In the case of including an oriented polymer, as the oriented polymer, for example, polyamides with amide bonds, gelatins, polyimides with imide bonds and polyamic acids, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates as their hydrolyzates can be cited. Among them, polyvinyl alcohol is preferred. Two or more oriented polymers can be combined.
[0136] An oriented film containing an oriented polymer is usually obtained by applying an oriented polymer composition obtained by dissolving the oriented polymer in a solvent to a substrate, removing the solvent to form a coating film; or applying the oriented polymer composition to a substrate, removing the solvent to form a coating film, and rubbing the coating film.
[0137] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer is completely dissolved in the solvent. The content of the oriented polymer in the oriented polymer composition is preferably 0.1% by mass to 20% by mass, more preferably 0.1% by mass to 10% by mass.
[0138] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTMER (registered trademark, manufactured by JSR Corporation).
[0139] As a method for applying the oriented polymer composition to a substrate, the same method as the method previously described as a method for applying a polymerizable liquid crystal composition liquid to a substrate can be cited. As a method for removing the solvent contained in the oriented polymer composition, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0140] The coating film formed of the oriented polymer composition may be subjected to a rubbing treatment. By performing the rubbing treatment, an orientation control force can be imparted to the coating film.
[0141] As a rubbing treatment method, for example, there can be mentioned a method of bringing the coating film into contact with a rubbing roller wound with a rubbing cloth and rotating. If masking is performed during the rubbing treatment, a plurality of regions (patterns) with different alignment directions can be formed on the alignment film.
[0142] The photo-alignment film is generally obtained by applying a photo-alignment film-forming composition containing a polymer or monomer having a photoreactive group and a solvent to a substrate, removing the solvent, and then irradiating with polarized light (preferably polarized UV light). The photo-alignment film can arbitrarily control the direction of the alignment control force by selecting the polarization direction of the irradiated polarized light.
[0143] Photoreactive groups refer to groups that generate liquid crystal orientation ability by light irradiation. Specifically, groups that participate in photoreactions such as orientation-inducing reactions, isomerization reactions, photodimerization reactions, photocrosslinking reactions, or photodecomposition reactions of molecules generated by light irradiation as the origin of orientation ability can be cited. As photoreactive groups, preferably, groups having unsaturated bonds, especially groups having double bonds, are particularly preferably groups having at least one selected from the group consisting of carbon-carbon double bonds (C=C bonds), carbon-nitrogen double bonds (C=N bonds), nitrogen-nitrogen double bonds (N=N bonds), and carbon-oxygen double bonds (C=O bonds).
[0144] As photoreactive groups having C=C bonds, for example, vinyl, polyene, stilbene, stilbazole, stilba zolium, chalcone and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, for example, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, for example, azophenyl, azonaphthyl, aromatic heterocyclic azo, bisazo, formazan and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, for example, benzophenone, coumarin, anthraquinone and maleimide groups can be cited. These groups may have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid and halogenated alkyl groups.
[0145] The group participating in the photodimerization reaction or the photocrosslinking reaction is preferred from the perspective of excellent orientation. Among them, the photoreactive group participating in the photodimerization reaction is preferred, and cinnamoyl and chalcone groups are preferred from the perspective of relatively small polarized light irradiation amount required for orientation and easy to obtain a photo-alignment film with excellent thermal stability and stability over time. As a polymer having a photoreactive group, a polymer having a cinnamoyl group such as a cinnamic acid structure at the terminal of the polymer side chain is particularly preferred.
[0146] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably set to at least 0.2 mass %, more preferably in the range of 0.3 mass % to 10 mass %. The composition for forming a photo-alignment film can contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly damage the properties of the photo-alignment film.
[0147] As a method for applying the photo-alignment film-forming composition to a substrate, the same method as the method for applying the oriented polymer composition to a substrate can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, the same method as the method for removing the solvent from the oriented polymer composition can be cited.
[0148] When irradiating polarized light, it can be in the form of directly irradiating polarized light to the composition for forming a photo-alignment film coated on the substrate by removing the solvent, or it can be in the form of irradiating polarized light from the substrate side and irradiating the polarized light through the substrate. In addition, it is preferred that the polarized light is substantially parallel light. For the wavelength of the irradiated polarized light, the wavelength region in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy is appropriate. Specifically, UV (ultraviolet light) in the range of 250nm to 400nm is particularly preferred. As a light source for irradiating the polarized light, ultraviolet lasers such as xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, etc. can be cited. Among them, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because of the large luminous intensity of ultraviolet rays with a wavelength of 313nm. The light from the aforementioned light source is passed through an appropriate polarizing layer and irradiated, so that polarized UV light can be irradiated. Examples of the polarizing layer include polarizing filters, polarizing prisms such as Glan-Thompson and Glan-Taylor, and wire-grid type polarizing layers.
[0149] In addition, when rubbing or polarized light irradiation is performed, if shielding is performed, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.
[0150] The groove alignment layer is a film having a concavo-convex pattern or multiple grooves on the film surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules are aligned in the direction along the grooves.
[0151] As methods for obtaining a groove orientation layer, the following methods can be cited: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a pre-cured UV-curable resin on a plate-shaped original plate having grooves on the surface, and then transferring the formed resin layer to a substrate and curing it; and a method of pressing a rolled original plate having a plurality of grooves onto a film of a pre-cured UV-curable resin formed on a substrate to form convex-concave and concave, and then curing it.
[0152] In the drying process, as a method for removing the solvent from the coating layer obtained in the coating process, for example, natural drying, ventilation drying, heating drying, reduced pressure drying and a combination thereof can be cited. Among them, natural drying or heating drying is preferred. The drying temperature is preferably in the range of 0°C to 200°C, more preferably in the range of 20°C to 150°C, and further preferably in the range of 50°C to 130°C. The drying time is preferably in the range of 10 seconds to 20 minutes, more preferably in the range of 30 seconds to 10 minutes.
[0153] In the curing step, the polymerizable liquid crystal compound aligned in the drying step can be polymerized by a known method for polymerizing a compound having a polymerizable functional group, for example, photopolymerization by irradiation with active energy rays can be employed.
[0154] As the active energy ray for irradiation, it is appropriately selected according to the type of polymerizable liquid crystal compound, the type of photopolymerization initiator when including a photopolymerization initiator, and their amount. Specifically, one or more lights selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays, and γ rays can be cited. Among them, from the aspect of easy control of the progress of the polymerization reaction and the aspect that a device widely used in the art as a photopolymerization device can be used, ultraviolet light is preferred, and the type of polymerizable liquid crystal compound is preferably selected in a manner that can be photopolymerized using ultraviolet light.
[0155] As the light source of the aforementioned active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0156] The UV radiation intensity is usually 10mW / cm 2 Above and 3,000mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and even more preferably 0.1 seconds to 1 minute. When irradiation is performed once or multiple times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 mJ / cm 2 Above and 3,000mJ / cm 2 Below, preferably 50mJ / cm 2 Above and 2,000mJ / cm 2 Below, more preferably 100 mJ / cm 2Above and 1,000mJ / cm 2 the following.
[0157] Example
[0158] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited thereto. In addition, the concentrations (volume % and mass %) and polymerization ratios described in this specification are calculated based on values measured by the same method as in the following Examples.
[0159] (Example 1)
[0160] Preparation of polymerizable liquid crystal composition liquid
[0161] The polymerizable liquid crystal compound (A) shown in the following formula was synthesized by the method described in Japanese Patent Application Publication No. 2010-31223. 100 parts by mass of the polymerizable liquid crystal compound (A), 0.1 parts by mass of a polyacrylate compound (leveling agent) (BYK-361N; manufactured by BYK-Chemie), 3 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butane-1-one (Irgacure 369 (Irg369); manufactured by BASF Japan Ltd.), and 0.1 parts by mass of butylated hydroxytoluene (hereinafter also referred to as "BHT") as a polymerization inhibitor were mixed in an atmosphere having an oxygen concentration of 0.1 to 4.0% by volume. N-methyl-2-pyrrolidone (NMP) was added to the obtained mixture in such a manner that the solid content concentration became 13%, and the mixture was stirred at 50°C for 1 hour to obtain a polymerizable liquid crystal composition liquid (1) containing the polymerizable liquid crystal compound (A).
[0162]
[0163] ·Filling and storage of polymerizable liquid crystal composition liquid into containers
[0164] Cover the entire surface of a 500 mL three-necked eggplant flask with aluminum foil to block light. Fill the shielded eggplant flask with 400 parts of the obtained polymerizable liquid crystal composition liquid (1) relative to the total capacity of 500 parts of the eggplant flask. The eggplant flask filled with the polymerizable liquid crystal composition liquid (1) is replaced with nitrogen and the oxygen concentration of the gas phase (i.e., 100 parts relative to the total capacity of 500 parts of the eggplant flask) is adjusted to 0.1 volume %, and heated in an oil bath at 80°C for 24 hours. After heating, the polymerizable liquid crystal composition liquid (1) is cooled to room temperature (25°C) to obtain a container (1) containing the polymerizable liquid crystal composition liquid.
[0165] The obtained container containing the polymerizable liquid crystal composition liquid was stored in a dark place at 23° C. for 1 month.
[0166] <Evaluation of Orientation>
[0167] Polyimide (SUNEVER, Nissan Chemical Products) was applied on a 4 cm × 4 cm glass substrate using a spin coater, dried at 80°C for 1 minute, and then subjected to a friction treatment to obtain an oriented film. The thickness of the obtained photo-oriented film was 100 nm. The polymerizable liquid crystal composition liquid (1) was taken out from a container containing the polymerizable liquid crystal composition liquid that had been stored in a dark place at 23°C for 1 month, and filtered using a filter (PTFE type) with a pore size of 0.2 μm at 40°C. The filtered polymerizable liquid crystal composition liquid (1) was applied on the aforementioned oriented film, dried at 120°C for 1 minute, and then irradiated with ultraviolet light from the coated side of the polymerizable liquid crystal composition liquid (1) using a high-pressure mercury lamp (under a nitrogen atmosphere, wavelength: 365 nm, the cumulative light amount at a wavelength of 365 nm is 500 mJ / cm 2 ), thereby forming a liquid crystal solidification layer, and obtaining a laminate comprising a liquid crystal solidification layer / orientation film layer / substrate (hereinafter also referred to as a "phase difference plate"). The obtained liquid crystal solidification layer was observed at a magnification of 400 times using a polarizing microscope (BX51, manufactured by Olympus Corporation). Those where no orientation defects were observed on the surface were recorded as "○", and those where orientation defects were observed on the surface were evaluated as "×". The results are shown in Table 1.
[0168] <Evaluation of hue>
[0169] The polymerizable liquid crystal composition liquid (1) stored at 23°C for 1 month was used to evaluate the color of the composition liquid according to "JIS K0071-2: 1998 Color test methods for chemicals - Part 2: Gardner color number". The hue of 2 to 4 was recorded as "0", 5 to 6 as "Δ", and 7 to 7 as "×". The results are shown in Table 1.
[0170] <Evaluation of Polymerization Rate>
[0171] The surface of the obtained retardation plate was subjected to infrared total reflection absorption spectrum measurement (incident angle 45°). The measured in-plane bending vibration (1408 cm -1 ) has a peak intensity I(1) of 0.0025, which is derived from the stretching vibration of the unsaturated bond of the aromatic ring (1504 cm -1 ) was 0.050. The P value of the surface irradiated with ultraviolet rays among the surfaces perpendicular to the thickness direction of the retardation plate was calculated (P = peak intensity I(1) / peak intensity I(2)) (P value = 0.050).
[0172] Similarly, a solution obtained by dissolving a polymerizable liquid crystal compound (A) in N-methyl-2-pyrrolidone was dried to obtain a single layer of the polymerizable liquid crystal compound (A). The obtained layer was not irradiated with light. The infrared total reflection absorption spectrum of the obtained layer was measured, and the P0 value as the P value of the polymerizable liquid crystal compound (A) was calculated, and the result was 0.3226.
[0173] According to the calculated P value and P0 value, the value of (1-P / P0)×100 is calculated, and the value is used as the polymerization rate (%) of the phase difference plate. According to the calculation method, the polymerization rate of the phase difference plate is 84.6%. Hereinafter, as an evaluation of the polymerization rate, the polymerization rate (%) calculated according to the above formula is 80 or more and is recorded as "0", and the one less than 80 is recorded as "×". The results are shown in Table 1.
[0174] (Example 2 and Example 3)
[0175] The content of BHT was set to 0.3 parts by mass or 1.0 parts by mass, respectively. Otherwise, the same operation as in Example 1 was performed to prepare polymerizable liquid crystal composition liquids (2) and (3). The same operation as in Example 1 was performed to prepare containers (2) or (3) filled with polymerizable liquid crystal composition liquids (2) and (3), respectively, and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquids (2) and (3), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0176] (Example 4)
[0177] The oxygen concentration of the gas phase in the container was adjusted to 1.0% by volume, and the solvent used in preparing the polymerizable liquid crystal composition liquid was changed to cyclopentanone (CYP). Otherwise, the same operation as in Example 2 was performed to prepare the polymerizable liquid crystal composition liquid (4). The same operation as in Example 1 was performed to prepare a container containing the polymerizable liquid crystal composition liquid (4) and filled with the polymerizable liquid crystal composition liquid (4), and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid (4), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0178] (Example 5)
[0179] The oxygen concentration of the gas phase in the container was adjusted to 10.0% by volume, and otherwise, a container (5) filled with the polymerizable liquid crystal composition liquid (1) was prepared in the same manner as in Example 1. The orientation of the liquid crystal solidified layer after storage in the container for 1 month, the hue of the polymerizable liquid crystal composition liquid in the container (5) containing the polymerizable liquid crystal composition liquid, and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated in the same manner as in Example 1. The results are summarized in Table 1.
[0180] (Example 6)
[0181] The oxygen concentration of the gas phase in the container was adjusted to 10.0% by volume, and otherwise, a container (6) filled with a polymerizable liquid crystal composition liquid (3) was prepared in the same manner as in Example 3. The orientation of the liquid crystal solidified layer after storage in the container for 1 month, the hue of the polymerizable liquid crystal composition liquid in the container (6) containing the polymerizable liquid crystal composition liquid, and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated in the same manner as in Example 1. The results are summarized in Table 1.
[0182] (Example 7)
[0183] The oxygen concentration of the gas phase in the container was adjusted to 5.0% by volume, and otherwise, a container (7) filled with the polymerizable liquid crystal composition liquid (1) was prepared in the same manner as in Example 5. The orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid in the container (7) containing the polymerizable liquid crystal composition liquid, and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated in the same manner as in Example 1 after being stored in the container for 1 month. The results are summarized in Table 1.
[0184] (Example 8 and Example 9)
[0185] The solvent used in preparing the polymerizable liquid crystal composition liquid was changed to propylene glycol monomethyl ether (PG ME) or propylene glycol monomethyl ether acetate (PGMEA), respectively. Except for this, the same operation as in Example 4 was performed to prepare polymerizable liquid crystal composition liquids (8) and (9). The same operation as in Example 1 was performed to prepare containers (8) and (9) containing polymerizable liquid crystal composition liquids filled with polymerizable liquid crystal composition liquids (8) or (9), respectively, and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquids (8) and (9), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0186] (Example 10)
[0187] The polymerizable liquid crystal compound (A) was changed to a polymerizable liquid crystal compound (B) having the following structure. The polymerizable liquid crystal composition liquid (10) was prepared in the same manner as in Example 4. The polymerizable liquid crystal composition liquid (10) was filled with the polymerizable liquid crystal composition liquid (10) and a container (10) containing the polymerizable liquid crystal composition liquid was prepared in the same manner as in Example 1. The orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid (10), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0188]
[0189] (Example 11)
[0190] The polymerizable liquid crystal compound (A) was changed to a polymerizable liquid crystal compound (C) having the following structure. The polymerizable liquid crystal composition liquid (11) was prepared in the same manner as in Example 4. A container (11) containing the polymerizable liquid crystal composition liquid (11) filled with the polymerizable liquid crystal composition liquid (11) was prepared in the same manner as in Example 1, and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid (11), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0191]
[0192] (Comparative Example 1)
[0193] The oxygen concentration of the gas phase in the container was not controlled, and the oxygen concentration was 21.0% by volume. In addition, the same operation as in Example 2 was performed to prepare a container (1') containing a polymerizable liquid crystal composition liquid filled with a polymerizable liquid crystal composition liquid (2). The orientation of the liquid crystal solidified layer after being stored in the container for 1 month, the hue of the polymerizable liquid crystal compound in the container (1') containing the polymerizable liquid crystal composition liquid, and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated in the same manner as in Example 1. The results are summarized in Table 1.
[0194] (Comparative Example 2)
[0195] The gas phase in the container was replaced with nitrogen so that the oxygen concentration became 0.01% by volume. In addition, the same operation as in Example 2 was performed to prepare a container (2') filled with a polymerizable liquid crystal composition liquid (2). The orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal compound in the container (2') containing the polymerizable liquid crystal composition liquid, and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated in the same manner as in Example 1 after being stored in the container for 1 month. The results are summarized in Table 1.
[0196] (Comparative Example 3)
[0197] The content of BHT was set to 0.6% by mass, except that the same operation as in Comparative Example 2 was performed to prepare a polymerizable liquid crystal composition liquid (3'). The same operation as in Example 1 was performed to prepare a container (3') containing a polymerizable liquid crystal composition liquid filled with the polymerizable liquid crystal composition liquid (3'), and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid (3'), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0198] (Comparative Example 4)
[0199] The content of BHT was set to 3.0% by mass, except that the same operation as in Example 4 was performed to prepare a polymerizable liquid crystal composition liquid (4'). The same operation as in Example 1 was performed to prepare a container (4') containing a polymerizable liquid crystal composition liquid filled with the polymerizable liquid crystal composition liquid (4'), and the orientation of the liquid crystal solidified layer, the hue of the polymerizable liquid crystal composition liquid (4'), and the polymerization rate of the polymerizable liquid crystal compound in the liquid crystal solidified layer were evaluated after being stored in the container for 1 month. The results are summarized in Table 1.
[0200] [Table 1]
[0201]
[0202] According to Table 1, it can be confirmed that in Examples 1 to 11 according to the present invention, the generation of polymers of the polymerizable liquid crystal compound during storage is suppressed, and the generation of orientation defects when the liquid crystal composition liquid is used to form a liquid crystal solidified layer can be prevented. In contrast, in Comparative Examples 1 to 4, orientation defects are generated in the liquid crystal solidified layer, or the polymerization rate is significantly reduced.
Claims
1. A container containing a polymerizable liquid crystal composition liquid, the container comprising a gas phase and a liquid phase formed of the polymerizable liquid crystal composition liquid, The polymerizable liquid crystal composition liquid comprises: a polymerizable liquid crystal compound; one or more solvents selected from the group consisting of a ketone solvent, an amide solvent, an ester solvent, and an ether solvent; a photopolymerization initiator; and a polymerization inhibitor in an amount of 0.1% by mass or more and 2% by mass or less relative to the polymerizable liquid crystal compound. The polymerization inhibitor comprises at least one selected from the group consisting of phenolic compounds and amine compounds, The oxygen concentration in the gas phase is greater than or equal to 0.1 volume % and less than or equal to 10 volume %.
2. The container containing the polymerizable liquid crystal composition liquid according to claim 1, wherein: The polymerizable liquid crystal compound has a (meth)acryloyl group.
3. The container containing the polymerizable liquid crystal composition liquid according to claim 1 or 2, wherein: The polymerizable liquid crystal compound exhibits maximum absorption in a wavelength range of 300 nm to 400 nm.
4. The container containing the polymerizable liquid crystal composition liquid according to claim 1 or 2, wherein: The total light transmittance of the container is 20% or less.
5. A method for storing a polymerizable liquid crystal composition liquid, comprising storing the polymerizable liquid crystal composition liquid in a container under an atmosphere having an oxygen concentration of 0.1 volume % or more and 10 volume % or less, wherein the polymerizable liquid crystal composition liquid comprises: a polymerizable liquid crystal compound; one or more solvents selected from the group consisting of a ketone solvent, an amide solvent, an ester solvent, and an ether solvent; a photopolymerization initiator; and an inhibitor in an amount of 0.1 mass % or more and 2 mass % or less relative to the polymerizable liquid crystal compound, The polymerization inhibitor includes one or more selected from the group consisting of phenolic compounds and amine compounds.
6. The method for storing a polymerizable liquid crystal composition liquid according to claim 5, wherein: Store in a container with a total light transmittance of 20% or less.
7. The method for storing a polymerizable liquid crystal composition liquid according to claim 5 or 6, wherein: Store at 10°C to 50°C.
